Avaliação da presença de ESBL, carbapenemase do tipo KPC e porinas como mecanismo de resistência em cepas de Klebsiella pneumoniae e Enterobacter spp. - Jaskulski, Mariluce da Rocha (2013)
The emergence and spread of resistance mechanisms in Gram-negative bacilli have complicate the treatment of serious nosocomial infections. Due to the ineffectiveness of the automated detection of KPC producer isolates there is a need to develop better methodologies. One possibility is to evaluate the ertapenem resistance, which has greater sensitivity to detect the expression of KPC producing isolates. However, the specificity may be reduced due to the resistance attributed to other mechanisms, such as AmpC gene expression or ESBL production associated with the loss of porin. This study included 128 samples of Gram-negative bacilli of Klebsiella pneumoniae and Enterobacter spp. resistant to ertapenem. Disk diffusion and E-test® method were applied to determine the susceptibility to imipenem, meropenem and ertapenem. Isolates intermediate and resistant to ertapenem were evaluated and additional resistance mechanisms conferred by blaTEM, blaSHV, blaCTX-M, blaCTX-M-2 and blaKPC for Klebsiella pneumoniae and Enterobacter cloacae genes were investigated by PCR technique. The presence of outer membrane protein (OMP) was investigated by dot blot. The gene blaTEM was detected in 52.9% and 10.3%; blaSHV in 29.4% and 0.94%; blaCTX-M in 41.4% and 1.9%, and blaCTX-M-2 in 23.5% and 1.9% of K. pneumoniae and Enterobacter cloacae isolates, respectively. blaKPC gene was present in 12.6% of Enterobacter spp. isolates. The OmpC and OmpF were present in 3.8% of Enterobacter cloacae isolates. Resistance genes and outer membrane proteins carbapenemases producing strains indicates that several resistance mechanisms contribute to therapeutic failure and point to the need for better detection methods and surveillance strategies.